Interpretation of Verses on the Law of Marriage between Muslims and Non-Muslims (Musyrik, Kafir and Ahl Al-Kitab) - Najib, Moh; Abdurrahman, U.; Sofyan, Ayi (Westscience Press, 2023)
The MUI's fatwa in the Second National Deliberation on May 26 – June 1, 1980, on Mixed Marriage stipulates that